PERAN PENGAWAS DALAM IMPLEMENTASI KURIKULUM 13 MATA PELAJARAN PAI (Studi Pada Pengawas guru PAI SMK Kab. Rejang Lebong) - Efi Hazizah (IAIN Bengkulu, 2019)
The role of Islamic religious education teacher supervisors is very strategic in maintaining Islamic education learning in order to remain on the right and more advanced track in the application of education to K13 for students. The reality in the field of PAI teacher supervisors in the Rejang Lebong is very minimal so the oversight range is very limited and supervisory competence is still very low. Due to the guidance of teachers in implementing character-based Islamic education in schools by GPAI supervisors, this study aims to delve deeper scientifically into how the role of the GPAI is in providing caregivers to the application of K13-based Islamic education. The required approach in this study is a qualitative approach, the research location is Rejang Lebong Vocational School, while GPAI supervisors, principals and Islamic religious education teacher became informants in this study, data were collected from research objects, observations, structured interviews and documentary studies, and analyzed by collecting data, the data is reduced then the data is presented in an analytical descriptive manner and finally conclusions are taken. After conducting research from various informants and other sources, conclusions were obtained: 1) Character-based Islamic Education in Rejang Lebong Vocational School incorporating the character values to be achieved in the Islamic religious education curriculum must be carried out through planning during the preparation of learning plans; 2) The GPAI supervisor has the role of conducting academic supervision in the implementation of the K13 based on the tupoksi of each supervisor that is carried out in accordance with the three aspects of supervision, namely planning, implementation and assessment. The supervisory techniques carried out were: individual supervision and group supervision as well as supervisory results in terms of managerial supervision, namely better change in the supervision of the implementation of learning and education personnel services and for students such as: habitual handshake every morning, reading the Qur’an every morning , Dhuhur prayer teaches in school, and Friday is clean and accustomed to practicing infaq, shodaqoh and others. The result of academic supervision is the implementation of more learning, both from lesson plans, methods, media and sources, the average value of students ‘religious studies increases and students’ religious behavior improves.